Impact of cognitive and linguistic ability on gaze behavior in children with hearing impairment - Sandgren, Olof; Andersson, Richard; van de Weijer, Joost; Hansson, Kristina; Sahlén, Birgitta (Frontiers in Psychology, 2013)
In order to explore verbal-nonverbal integration, we investigated the influence of cognitive and linguistic ability on gaze behavior during spoken language conversation between children with mild-to-moderate hearing impairment (HI) and normal-hearing (NH) peers. Ten HI-NH and ten NH-NH dyads performed a referential communication task requiring description of faces. During task performance, eye movements and speech were tracked. Cox proportional hazards regression was used to model associations between performance on cognitive and linguistic tasks and the probability of gaze to the conversational partner’s face. Analyses compare the listeners in each dyad (HI: n = 10, mean age = 12;6 years, SD = 2;0, mean better ear pure-tone average 33.0 dB HL, SD = 7.8; NH: n = 10, mean age = 13;7 years, SD = 1;11). Group differences in gaze behavior – with HI gazing more to the conversational partner than NH – remained significant despite adjustment for ability on receptive grammar, expressive vocabulary, and complex working memory. Adjustment for phonological short term memory, as measured by nonword repetition, removed group differences, revealing an interaction between group membership and nonword repetition ability. Stratified analysis showed a twofold increase of the probability of gaze-to-partner for HI with low phonological short term memory capacity, and a decreased probability for HI with high capacity, as compared to NH peers. The results revealed differences in gaze behavior attributable to performance on a phonological short term memory task. Participants with hearing impairment and low phonological short term memory capacity showed a doubled probability of gaze to the conversational partner, indicative of a visual bias. The results stress the need to look beyond the hearing impairment in diagnostics and intervention. Acknowledgment of the finding requires clinical assessment of children with hearing impairment to be supported by tasks tapping phonological processing.